A National Analysis of State Policies on Lesbian, Gay, Bisexual, Transgender, and Questioning/Queer Inclusive Sex Education. (13th December 2020) - Garg, Namrata; Volerman, Anna
ABSTRACT: BACKGROUND: Many youth engage in risky sexual behaviors that are associated with adverse sexual health outcomes. Lesbian, gay, bisexual, transgender, and questioning/queer (LGBTQ) youth are disproportionately affected. Comprehensive sex education is instrumental to minimize these outcomes; however, each state varies in the topics taught. METHODS: This paper is a comprehensive review of all 50 states and the District of Columbia's policies, including laws and education standards, for LGBTQ inclusive material in school‐based sex education for youth in K‐12. RESULTS: Overall, 48 states have policies that mandate sex education in the public schools. This review describes policy differences relevant to students who identify as LGBTQ, by comparing required topics, parental/guardian permission, LGBTQ inclusion, and normative language requirements. CONCUSIONS: There is a lack of uniformity and presence of discrimination in school‐based sex education policies in the United States, particularly related to LGBTQ topics. Therefore, young people, especially LGBTQ students, face geographical barriers to accessing sexual health information and schools are limited in implementing curriculum essential for students to optimize sexual health outcomes. State policymakers, school administrators, child health advocates, and parents should work to eliminate barriers for comprehensive sex education.